Vivências de casais homoparentais: percepções e desafios no processo educacional escolar. “Mas era tudo velado” - Santos, Jonas da Fonseca (2023)
This research was developed aiming to identifying the barriers faced by homoparental families in the social insertion of their children in private schools in João Pessoa, and to what extent an educational proposal that encompasses diversity can transform this group and possible social relationships, through the interfamily relationships in conjunction with educational institutions. Society, within its patriarchal, conservative structure and with potentially discriminatory structuring discourses, does not contribute to the development of a harmonious construction, directly affecting homoparental families. Consequently, members rooted in a culture or traditional family model return to society, which does not add up to a profound change in a positive sense. Bearing this in mind, fieldwork was carried out with interviews with homoaffective families, whose statements covered their experiences and perceptions of sociability. This research has a qualitative nature and was based on Michel Foucalt's literature, with post-structuralist bibliographical references that also served as a basis for the analysis of the interviews. In general, the interviews indicated experiences of prejudice and exclusion associated with intra and extraschool aspects, however, they also illustrate individual and collective strategies of resistance.